Disseleneto de difenila e selenito de sódio associado à trimetoprima e sulfametoxazol em toxoplasmose experimental: influência na atividade de biomarcadores de estresse oxidativo e modulação de citocinas - Barbosa, Cleber Francisco (2014)
Toxoplasmosis is a zoonosis of worldwide geographic distribution, caused by Toxoplasma gondii, an obligate intracellular protozoan with, in certain regions, high-impact medical-veterinary; being considered one of the most widespread infectious diseases. The aim of this study was to assess the effect of sulfamethoxazole and trimethoprim (ST) associated with diphenyl diselenide (DPDS) and sodium selenite (SSe) in experimental toxoplasmosis, on oxidant/antioxidant biomarkers and cytokine levels. Therefore, this study evaluated the levels of thiobarbituric acid reactive substances (TBARS), advanced oxidation protein products (AOPP) and glutathione reductase (GR), as well as on the modulation of inflammatory response through assessment of INF-γ and IL-10. For that eighty four adult male BALB/c mice were used, divided in two seven groups. Group A was used as negative control. The mice from groups B to G were infected intraperitoneally with 1.2x107 tachyzoites (RH strain). Of these, the group B represented the positive control; groups C to G represented the treatment groups, as follow: C: T. gondii plus ST; D: T. gondii supplemented by SSe; E: T. gondii plus DPDS; F T. gondii treated with ST associated with SSe; and G: T. gondii plus ST associated with DPDS. Samples of blood and liver were collected and analyzed on days 4 and 20 post-infection (p.i.). As results, it was possible to observe that TBARS levels significantly increased (P<0.05) in groups B, C and F on day 4 p.i., while it was reduced (P<0.05) in groups C, F and G on day 20 p.i. when these data were compared with group A. Levels of AOPP significantly increased (P<0.001) in groups C and G on day 4 p.i., and it was reduced in groups C, F and G (P<0.001) on day 20 p.i. when compared with group A. Additionally, the activity of GR significantly (P<0.01) increased on day 4 p.i. in group G when it was compared with the control group. Cytokine levels showed INF- significantly increased (P<0.001) in both periods, day 4 (groups B, C, F and G) and 20 p.i. (groups C, F and G) when compared with group A. Levels of IL-10 were significantly reduced (P<0.001) on day 4 p.i. in group B, while at the same period it was increased (P<0.001) in groups C and G when compared with group A. On day 20 p.i. IL-10 had its levels increased (P<0.001) in groups F and G, when compared with control group. Therefore, our results highlighted that inorganic (sodium selenite) and organic (diphenyl diselenide) forms of selenium associated with the chemotherapy (a common therapeutic choice in toxoplasmosis) were able to reduce the lipid peroxidation and protein oxidation, manly during the acute phase of the experimental infection, as well as it provided a immunologic balance between the production of pro and anti-inflammatory cytokines, avoiding over production of pro-inflammatory cytokines.